Query-by-Example Music Information Retrieval by Score-Informed Source Separation and Remixing Technologies. (17th January 2011) - Itoyama Itoyama, Katsutoshi Katsutoshi; Goto Goto, Masataka Masataka; Komatani Komatani, Kazunori Kazunori; Ogata Ogata, Tetsuya Tetsuya; Okuno Okuno, Hiroshi G. Hiroshi G.
Abstract : We describe a novel query-by-example (QBE) approach in music information retrieval that allows a user to customize query examples by directly modifying the volume of different instrument parts. The underlying hypothesis of this approach is that the musical mood of retrieved results changes in relation to the volume balance of different instruments. On the basis of this hypothesis, we aim to clarify the relationship between the change in the volume balance of a query and the genre of the retrieved pieces, called genre classification shift . Such an understanding would allow us to instruct users in how to generate alternative queries without finding other appropriate pieces. Our QBE system first separates all instrument parts from the audio signal of a piece with the help of its musical score, and then it allows users remix these parts to change the acoustic features that represent the musical mood of the piece. Experimental results showed that the genre classification shift was actually caused by the volume change in the vocal, guitar, and drum parts.